A 0.5 μA/Channel front-end for implantable and external ambulatory ECG recorders. (April 2018) - Rezaeiyan, Yasser; Zamani, Milad; Shoaei, Omid; Serdijn, Wouter A.
Abstract: There is an increasing demand for low power, low voltage, and small size analog readout bio-potential systems. This paper presents an analog front-end for measuring the intra-cardiac signals in implantable and also external ambulatory ECG cardiac recording applications. The analog front-end benefits from voltage to frequency conversion without conventional analog to digital conversion and thereby achieves a very low power consumption. The frequency averaging digital reconstruction makes an intrinsic low pass filter of which the cut-off frequency changes with the averaging interval and eliminates the need for an analog filter in this system. Furthermore, this feature enables the development of a general purpose analog readout bio-potential measurement system with programmable bandwidth. The proposed IC is fabricated in a 0.18 μm CMOS process and occupies 0.396 mm 2 . It can measure intra-cardiac bio-potentials with 9.2-bit resolution while consuming just 0.5 μA per channel from a 1 V supply. The input referred noise of the intra-cardiac signal readout channel is 2 μVrms .